THEORETICAL AND PRACTICAL STARTING POINTS OF MATHEMATICAL LINGUISTICS - Gyulzatyan, Davit (Foreign Languages for Special Purposes, 2023)
The interdisciplinary existence of mathematical linguistics is due to the possibility provided by the logical layer of language. Mathematics is the superstratum of language, a highly abstract metalanguage based on the language system. The mathematical principle is present in the language in proportion to different sections of mathematical science, that is, the mathematical patterns of the language can be extracted from geometrical, algebraic, combinatory, probabilistic and other points of view. Applying a mathematical arsenal to a language is not an end in itself. Due to the application of mathematical methods, linguistics achieves greater reliability and verification of the identification of linguistic patterns. The relevance of this article is determined by this conceptual observation. The aim of the work is to highlight the role of mathematical linguistics in fixing and making sense of the accuracy of language patterns with theoretical and practical starting points. The problem arising from the goal is to reveal the systematicity of patterns of both human language and private language with the help of mathematical methods from the viewpoints of coercibility and probability. The novelty of the work is the attempt to bring up the considered interdisciplinarity with a new twist, due to the reality of presenting the goal and problem in a new way. In addition to mathematical methods, general logical, semiotic and philosophical (particularly dialectical) methods were used in the work.
Keywords: Ontological levels of language; geometric principle; events; theorem; deductive tree; base; morpheme; combinatorics